2020
DOI: 10.21082/ijas.v21n1.2020.p1-10
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Heritability Estimate of 30 Rice Landraces of Lamjung and Tanahun Districts, Nepal

Abstract: The variability in the rice landraces is the source of variation and offers substantial opportunity for the development of new varieties through the selection. Exploring diversity and variability of landraces is utmost for rice improvement. The objective of the study was to assess diversity indices, magnitude of genetic variability, heritability, genetic advance for the yield, and yield contributing traits. An experiment was carried out in alpha-lattice with 30 landraces, two replications in the Agronomy far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
4
6
0
Order By: Relevance
“…In this study also, the first principal component shows that landraces like Lekali Marsi, Thakali Lahare Marsi, Indrabeli, and Baryang Masino have a high elongation ratio which means they can fetch premium price in the market. A study on rice landraces from Lamjung and Tanahun districts reported wide diversity and huge variability for agromorphological characteristics of those landraces and suggested their utilisation in future breeding programme [31]. Thus, the result from this study in combination with similar other studies related to agromorphological characteristics can be a foundation for molecular study.…”
Section: Discussionsupporting
confidence: 51%
“…In this study also, the first principal component shows that landraces like Lekali Marsi, Thakali Lahare Marsi, Indrabeli, and Baryang Masino have a high elongation ratio which means they can fetch premium price in the market. A study on rice landraces from Lamjung and Tanahun districts reported wide diversity and huge variability for agromorphological characteristics of those landraces and suggested their utilisation in future breeding programme [31]. Thus, the result from this study in combination with similar other studies related to agromorphological characteristics can be a foundation for molecular study.…”
Section: Discussionsupporting
confidence: 51%
“…While selecting a landrace as a parent in a breeding program, other numerous factors need to be considered. us, the result from this study along with the result of Pokhrel et al [5]; Sharma et al [26], and Dhakal et al [9] can set a foundation for future rice breeding programs. Further study at the gene level can be carried out to study the variation at the genetic level.…”
Section: Mahalanobis Distancesupporting
confidence: 53%
“…Rice landraces are the reservoir of genetic potential and several resistant genes for biotic and abiotic stress, whereas the modern varieties are devoid of such quality [8]. Landraces are more adapted to local conditions, have a higher chance of survival and reproduction, and pass on their characteristics to the next generation [9].…”
Section: Introductionmentioning
confidence: 99%
“…High PCV and GCV was expressed by the traits such as Na + /K + ratio (59.33%, 57.66%), grain yield per plant (31.11%, 30.54%), number of grains per panicle (28.59%, 28.54%), number of productive tillers per plant (23.75%, 22.99%) and 1000 grain weight (23.20%, 23.07%). Similar findings were reported by Dhakal et al, (2020) for number of productive tillers per plant, Kumar et al, (2020) for number of grains per panicle and Devi et al, (2020) for 1000 grain weight and grain yield per plant and Keerthana et al, (2019) for Na + /K + ratio.…”
Section: Resultssupporting
confidence: 88%